2014
DOI: 10.1016/j.celrep.2014.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analysis of Drosophila Circular RNAs Reveals Their Structural and Sequence Properties and Age-Dependent Neural Accumulation

Abstract: Circularization was recently recognized to broadly expand transcriptome complexity. Here, we exploit massive Drosophila total RNA-sequencing data, >5 billion paired-end reads from >100 libraries covering diverse developmental stages, tissues and cultured cells, to rigorously annotate >2500 fruitfly circular RNAs. These mostly derive from back-splicing of protein-coding genes and lack poly(A) tails, and circularization of hundreds of genes is conserved across multiple Drosophila species. We elucidate structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

64
951
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 849 publications
(1,037 citation statements)
references
References 37 publications
64
951
1
2
Order By: Relevance
“…In addition to alternative splicing, both the aging brain and Drosophila photoreceptors show increased levels of noncanonical splicing events such as circRNA formation (Gruner, Cortes‐Lopez, Cooper, Bauer, & Miura, 2016; Hall et al, 2017; Westholm et al, 2014). CircRNAs result from back‐splicing events from protein‐coding genes and can accumulate to much higher levels than their associated linear transcript (Wilusz, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to alternative splicing, both the aging brain and Drosophila photoreceptors show increased levels of noncanonical splicing events such as circRNA formation (Gruner, Cortes‐Lopez, Cooper, Bauer, & Miura, 2016; Hall et al, 2017; Westholm et al, 2014). CircRNAs result from back‐splicing events from protein‐coding genes and can accumulate to much higher levels than their associated linear transcript (Wilusz, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…An upgraded computational pipeline for circRNA annotation Multiple computational methods have been recently developed to detect back-splice junctions for circRNA annotation (Memczak et al 2013;Hoffmann et al 2014;Westholm et al 2014;Zhang et al 2014). Our previously reported pipeline, CIRCexplorer (Zhang et al 2014), has been reported as one of the best pipelines for circRNA annotation by identifying backsplice junctions (Hansen et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, circRNAs were rediscovered and shown to be the products of thousands of loci in eukaryotes, from fly and worm to mouse and human (Jeck et al 2013;Memczak et al 2013;Salzman et al 2013;Guo et al 2014;Westholm et al 2014;Zhang et al 2014;Ivanov et al 2015). Recent research into circRNA biogenesis has shown that backsplicing is catalyzed, though inefficiently (Zhang et al 2016), by the canonical spliceosomal machinery (Ashwal-Fluss et al 2014;Starke et al 2015;Wang and Wang 2015) and modulated by both cis-elements and trans-factors (Ashwal-Fluss et al 2014;Zhang et al 2014;Conn et al 2015;Ivanov et al 2015;Starke et al 2015; for review, see Chen and Yang 2015;Chen 2016).…”
mentioning
confidence: 99%
“…55,56 Further examples of RNA circularization by T4 Rnl1 include the synthesis of an infectious circRNA of the citrus exocortis viroid strain A (CEV-A), 57 circular versions of the hammerhead ribozyme, 58 and others more. 19 Apart from intrinsic secondary structure elements that help to orient the 2 termini to be ligated close to each other, proper orientation of the reactive ends can be achieved by using a splint that by hybridization with both the donor and the acceptor brings the substrates close together, however, leaves the terminal 2 to 3 nucleotides of both strands single stranded at the ligation junction (Fig. 2c).…”
Section: Enzymatic Strategiesmentioning
confidence: 99%
“…4,7,[14][15][16][17][18] Thus, circRNAs have also been considered as biomarkers for diseases prognostics and diagnostics and as targets or tools for disease treatment. [19][20][21] The field of investigations into circRNA and in particular into their putative function within the complex network of regulation of gene expression and splicing is currently very active. In addition to the technical and conceptual challenges, raised for example by sequence overlap with mRNA or linear noncoding RNA transcribed from the same locus, synthetic circRNAs are needed as models for structure and function studies.…”
Section: Introductionmentioning
confidence: 99%